Resisting the Heartbreak of Neoliberalism in Education Advocacy - Farhadi, Beyhan (Critical Education)

(untitled) (Institute for Critical Education Studies / UBC, 2024)
This paper explores how advocates in Ontario have resisted neoliberal restructuring in education since the 2018 general election, which marked an intensification of market-oriented reforms. Shaped by the insights of 23 participants, this paper shows how resistance has been accessed through multiple entry points and has been spatially heterogeneous, replete with internal contradiction. It also highlights the cost of resistance for participants whose relationship to systems engender oppression and harm. Broadly, this paper calls for vulnerable reflection on fantasies of a “good life” shaped by a normative neoliberal order that interferes with collective flourishing. Through emergent strategy, which aligns action with a vision for social justice, this paper values the non-linear and manifold ways individuals are embedded in systems; the fractal nature of change, which takes place at all scales; and a love ethic, which sustains relational the spiritual growth necessary for solidarity.